A-DInSAR technique applied to the surface displacements of the GW sector of the Brucutu mine – Quadrilátero Ferrífero - Boulhosa, Gabrieli Santos [UNESP]; Hartwig, Marcos Eduardo; Fernandes, Adam Barros (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
The Brucutu mine is in the northeast portion of the Quadrilátero Ferrífero, in the municipality of São Gonçalo do Rio Abaixo, approximately 120 km east of Belo Horizonte, Minas Gerais. In this place, Vale S.A. operates one of the largest iron ore mines in Brazil. Iron ore is housed in itabirite and hematite bodies of the Cauê Formation. These rocks have different geomechanical behaviors, since they occur in contact with intrusive rocks and are breached, intensely foliated and strongly weathered. The slopes of the quotas 1,030 to 1,000, of the GW sector of the Brucutu pit, have been registering instabilities in recent years. The present study aimed to analyze the superficial displacements and discuss the probable controlling factors. The Advanced Differential Radar Interferometry (A-DInSAR) technique was used from images of the COSMO-SkyMed sensor in StripMap mode to monitor the displacements. The periods covered for the development of this work were from June 2018 to August 2019 and from June 2019 to November 2020. The images used were provided and processed by the company Telespazio Brasil. Orthoimages from Remotely Piloted Aircraft (RPA), field geological-geotechnical data, and rainfall data were also used. The results obtained through A-DInSAR monitoring show that considerable displacement rates (up to -76.3 mm/year) were identified in the rainy season. The instabilities present in the study area are conditioned by the following factors: contact between intrusive rocks (IN) and friable itabirite (FI); unfavorable attitude of foliation; and high rainfall rates that produce the dismantling (erosion) of the slope face.
Técnica A-DInSAR aplicada aos deslocamentos superficiais do setor GW da mina de Brucutu – Quadrilátero Ferrífero
Keywords: Mine slopes; Rainfall; Slope instabilities